THE KNOWLEDGE OF NON PILGRIMS INTERNATIONAL TRAVELERS ABOUT WAYS OF TRANSMISSION AND PREVENTION OF AIDS - Nooritajer, M; Emamy, A; Dabbaghi, F; Kamali, P (Iran University of Medical Sciences, 2001)
Background : International travelers are one of those groups who are in danger of affecting with AIDS. They should be informed about it's risk factors. It is not important where the travelers intend to go, but it is important that they have information about ways of transmission and prevention of AIDS.   Objective : To determine knowledge of non pilgrims international travelers about the ways of transmissions and prevention of AIDS.   Design : This was a cross- sectional study. Data were collected through questionnaire.   Samples : 200 non pilgrims travelers were selected randomly.   Results : The findings indicated that the knowledge of non pilgrims travelers about ways of transmissions and prevention of AIDS was in middle range.   Conclusion : Research findings showed that the knowledge of travelers intending to go abroad are not enough about transmission and prevention of AIDS. In order to protect their health their knowledge should be increased through education.